Plan estratégico y su incidencia en la gestión administrativa de la empresa Desarrollo del Talento Humano Consultores E.I.R.L., Trujillo - 2015 - Maggio Castillo, Renzo Joeddy (2016)
This study was done to develop an Strategic Plan, which allows to improve The Administrative Management of Desarrollo del Talento Humano Consultores E.I.R.L company. To that effect, it started with gathering information about the company through historic data review, documents and interviews conducted to company’s senior management. After that, is was elaborated an internal and external study from the company, which was the basis to subsequent development of matrices (EFI Matrix, EFE Matrix, Internal / External Matrix, PEYEA Matrix, FODA Matrix, between others) of our strategic plan. After our matrices was developed, it fixed the objectives and goals to reach, with this is starts The Strategic Plan inside the company. From the results obtained in this study, it can be concluded, that the strategic plan in Desarrollo del Talento Humano Consultores E.I.R.L company impacted positively in the Administrative Management’s improvement, the improvement was reflected in economic profitability and working satisfaction, which was obtained from the employees. Besides that, it’s necessary to mention, that was not reached the goal from the all proposed objectives, because of the objectives related to costs had a negative influence: external economic factors and the rising from exchange rate of dollar and inflation. Because of that, its recommended exert more control and monitoring if activity programs form the Strategic Plan, in order to reach all proposed objectives.